Cerebral hemiatrophy unveiled: An in-depth radiological perspective on the diagnosis and clinical implications of Dyke-Davidoff-Masson syndrome - Rakshanda Agrawal, MBBS; Vaishali Dhawan, MBBS; Pratapsingh Parihar, MBBS; Anjali Kumari, MBBS; Komal Mishra, MBBS (Radiology Case Reports)
Dyke-Davidoff-Masson Syndrome (DDMS) is a rare neurological condition characterized by unilateral cerebral atrophy and compensatory cranial changes. It typically presents with a constellation of clinical features, including seizures, developmental delays, and hemiparesis, resulting from early brain injury or developmental anomalies. Radiological imaging, particularly Magnetic Resonance Imaging (MRI), plays a pivotal role in diagnosing DDMS by providing detailed visualization of the structural abnormalities and associated compensatory changes. This case report details the clinical and radiological findings of an 8-year-old female presenting with recurrent seizures, developmental delay, and left-sided hemiparesis. A neurological examination revealed cognitive impairment and significant left-sided weakness. Routine laboratory investigations were unremarkable, and an electroencephalogram (EEG) demonstrated focal epileptic activity. MRI findings were characteristic of DDMS, showing marked atrophy of the right cerebral hemisphere, ex vacuo dilatation of the lateral ventricle, ipsilateral calvarial thickening, and hyper pneumatization of the right sphenoid bone and bilateral mastoid air cells. Areas of cystic encephalomalacia with surrounding gliosis were noted in the right fronto-parieto-temporal regions, suggestive of prior ischemic or hypoxic injury. This case underscores the essential role of radiological imaging in diagnosing and managing DDMS. MRI confirms the diagnosis by highlighting hallmark features and helps differentiate it from other conditions with overlapping clinical and imaging findings, such as Sturge-Weber syndrome or Rasmussen encephalitis. Early recognition and diagnosis allow for optimized therapeutic strategies, including seizure management with antiepileptic medications and physiotherapy for motor deficits. Long-term follow-up is critical to monitor disease progression and adapt treatment plans.